Faktor-Faktor Penyumbang NEET di Provinsi Jawa Barat - Hella Citra (Badan Riset dan Inovasi Daerah Provinsi Kalimantan Selatan, 2022)
NEET (Not in Education, Employment, or Training) is one of the SustainableDevelopment Goals (SDGs) indicators to determine the level of vulnerability of youngpeople aged 15-24 years in dropping out of school, unemployment and feeling hopelessabout the world of work. BPS data shows that in 2020 West Java is the province with thehighest number of NEETs in Indonesia. The influence of West Java's NEET is very largeon the national NEET figure, as evidenced in the last 5 years the pattern is always thesame as West Java's NEET. For this reason, this study aims to determine the cause of aperson's chance to become a NEET in West Java Province using data from the 2020National Labor Force Survey (Sakernas). The analytical method used is descriptivestatistics and inferential statistics with binary logistic regression models. The resultsshowed that with a 95 percent confidence level, the variables that significantly affect aperson's status as a NEET are age, gender, disability, marital status, education, skills,work experience, education of the head of the household, number of children, presenceof toddlers or the elderly, presence of household members who work, location ofresidence, and the perceived impact of COVID-19. In addition, it was found that personswith disabilities were 4 times more likely to become NEETs than non-disabled persons. Abstrak NEET (Not in Education, Employment, or Training) ialah salah satu indikator Sustainable Development Goals (SDGs) untuk mengetahui tingkat kerawanan penduduk muda usia 15-24 tahun dalam putus sekolah, pengangguran serta merasa putus asa terhadap dunia kerja. Data BPS menunjukkan bahwa pada tahun 2020 Jawa Barat merupakan provinsi dengan jumlah NEET tertinggi di Indonesia. Pengaruh NEET Jawa Barat sangat besar terhadap angka NEET nasional, terbukti dalam 5 tahun terakhir polanya selalu sama dengan NEET Jawa Barat. Untuk itu, penelitian ini bertujuan untuk mengetahui penyebab seseorang berpeluang menjadi NEET di Provinsi Jawa Barat dengan menggunakan data Survei Angkatan Kerja Nasional (Sakernas) tahun 2020. Metode analisis yang digunakan adalah statistik deskriptif dan statistik inferensia dengan model regresi logistik biner. Hasil penelitian menunjukkan bahwa dengan tingkat kepercayaan 95 persen, variabel yang signifikan mempengaruhi status seseorang menjadi NEET ialah umur, jenis kelamin, disabilitas, status perkawinan, pendidikan, keterampilan, pengalaman kerja, pendidikan kepala rumah tangga, jumlah anak, keberadaan balita atau lansia, keberadaan anggota rumah tangga yang bekerja, lokasi tempat tinggal, dan dampak covid-19 yang dirasakan. Selain itu ditemukan penyandang disabilitas 4 kali lebih berisiko menjadi NEET dibandingkan dengan yang bukan penyandang disabilitas.